2017
DOI: 10.1212/wnl.0000000000003564
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate, cognition, and epilepsy

Abstract: This study provides Class II evidence that single doses of MPH improve cognitive performance on some measures of attention and processing speed in patients with epilepsy and cognitive complaints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 38 publications
2
7
0
2
Order By: Relevance
“…There has been increasing emphasis on screening and early identification of these problems, but critical are systematic intervention trials to improve life status. Unfortunately, there are few non-pharmacological intervention that have been demonstrated to be successful in epilepsy patients (Adams et al, 2017). These are slowly beginning to appear and will increase in the future (Jackson, Makin, & Baker, 2015; Ramaratnam, Baker, & Goldstein, 2008) and will be critical to improving patient life outcomes.…”
Section: Where Is the Neuropsychology Of Epilepsy Headed During The Nmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been increasing emphasis on screening and early identification of these problems, but critical are systematic intervention trials to improve life status. Unfortunately, there are few non-pharmacological intervention that have been demonstrated to be successful in epilepsy patients (Adams et al, 2017). These are slowly beginning to appear and will increase in the future (Jackson, Makin, & Baker, 2015; Ramaratnam, Baker, & Goldstein, 2008) and will be critical to improving patient life outcomes.…”
Section: Where Is the Neuropsychology Of Epilepsy Headed During The Nmentioning
confidence: 99%
“…Although there has been increasing emphasis on screening and early identification of comorbidities, there is a clear need for systematic intervention trials to improve practice and patient outcomes. Appearing are reports of interventions designed to improve memory and cognition (Adams et al, 2017; Caller et al, 2016; Del Felice et al, 2017; Farina, Raglio, & Giovagnoli, 2015; Jackson, Makin, & Baker, 2015), mood disorders (Gandy, Sharpe, & Perry, 2013), and epilepsy self-management (Jobst & MEW network, 2017; Shegog et al, 2013; Wagner et al, 2017). Both pharmacologic and behavioral interventions will be critical to improving patient life outcomes in patients with chronic epilepsy (Del Felice et al, 2017) and those who have undergone epilepsy surgery (Mazur-Mosiewicz et al, 2015).…”
Section: Where Will (Should) Neuropsychology Head During the Next Decmentioning
confidence: 99%
“…Efek OAE dapat meningkatkan stres oksidatif pada otak yang menyebabkan kerusakan neuronal hingga terjadinya suatu gangguan kognitif pada penyandang epilepsi. 34 Efek OAE bersifat fleksibel; bila obat tersebut dihentikan maka gangguan fungsi kognitif berangsur membaik. 33,34 Penyandang epilepsi harus minum obat secara rutin.…”
Section: Bahasanunclassified
“…34 Efek OAE bersifat fleksibel; bila obat tersebut dihentikan maka gangguan fungsi kognitif berangsur membaik. 33,34 Penyandang epilepsi harus minum obat secara rutin. Pengawasan ketat meminum obat oleh keluarga dapat membantu prognosis yang sejalan dengan penelitian yang dilakukan Oktaviana et al 35 yang meloprkan adanya hubungan kuat antara dukungan keluarga dan kepatuhan minum obat Dalam pemeriksaan MMSE (Tabel 3), sebagian besar pasien mangalami gangguan memori diikuti dengan atensi.…”
Section: Bahasanunclassified
“…A Swedish study involving more than 21,000 children with seizures, showed no evidence of increased risk of seizures from ADHD medications [61]. Preliminary findings in people with epilepsy also suggest that methylphenidate may be an effective and safe option for improving cognition and quality of life [62]. These data suggest that stimulants, methylphenidate in particular, can be safely used in the context of PTE but more studies are needed.…”
Section: Is the Management Of Psychiatric Disorders In Pte Different mentioning
confidence: 98%